The didactic dimension of mythological figures in Greek literature and scholia - Czerwińska, Jadwiga (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper discusses the types of heroes and anti-heroes established in literature by ancient Greek culture. In order to provide a full treatment of the subject, which in its diachronic aspect is very broad, the field of research has been limited. As a result, the present paper analyzes examples of mythological figures in the epic poems of Homer in juxtaposition with those found in Euripidean drama. The two authors have been chosen in view of the fact that their works are model representations of the values of their times as well as of the noticeable differences between them in evaluating the same mythological figures.